Home-Range and Activity Patterns of the South American Subterranean Rodent Ctenomys talarum - Cutrera, Ana Paula (2006)
Subterranean rodents are characterized by limited individual mobility and patchy distribution of local populations, all of which have been related to the great evolutionary diversification of this group. Because of their secretive habits, radiotracking becomes an essential tool to collect data systematically on characteristics of their space use, rate of movement, and daily patterns of activity. Compared to other subterranean species, the ctenomyids exhibit more activity above the surface. Despite this, a previous study showed that only 25% of the captive individuals analyzed presented rhythmic bouts of activity associated with light–dark cycles. In our study, we used radiotelemetry to explore quantitatively the home-range dynamics and daily movements of the South American Talas tuco-tuco (Ctenomys talarum). As expected, the home ranges of males were larger than those of females. However, intraspecific variation in home-range size also was observed between 2 different study sites, possibly reflecting differences in body size and soil characteristics between the study sites. Rhythmicity in activity patterns was confirmed to be polymorphic in this species, as previously observed in captivity, and daily activity was mostly concentrated in the diurnal period. We suggest that the present study will contribute to generating important insights into home-range dynamics and daily patterns of activity of free-living subterranean rodents.